Nash equilibria in the context of convex sets - Sūdžiūtė, Daina (Lietuvos matematikos rinkinys, 2001)
Nash equilibria (α, β),  α > O, β > O, are investigated in bimatrix (3 x 3) game. Necessary and sufficient conditions for existing of such Nash equilibria are obtained (in theorems 4 and 8), and the algorithms for calculating them too. Some ideas of convex analysis are employed.